2021
DOI: 10.1038/s41593-020-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Medial preoptic area antagonistically mediates stress-induced anxiety and parental behavior

Abstract: Anxiety is a negative emotional state that is overly displayed in anxiety disorders and depression. Although anxiety is known to be controlled by distributed brain networks, key components for its initiation, maintenance and coordination with behavioral state remain poorly understood. Here, we report that anxiogenic stressors elicit acute and prolonged responses in glutamatergic neurons of mouse medial preoptic area (mPOA). These neurons encode extremely negative valence, and mediate induction and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 52 publications
4
70
0
Order By: Relevance
“…A previous study showed that vgat neurons, a subset of GABAergic neurons, in the MPA encode positive value ( Zhang et al, 2021 ). Indeed, we recapitulated the results from the RTPP and open field tests in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study showed that vgat neurons, a subset of GABAergic neurons, in the MPA encode positive value ( Zhang et al, 2021 ). Indeed, we recapitulated the results from the RTPP and open field tests in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although these results may tentatively suggest that MPA vgat –vPAG is not necessary for exploration, it is important to note that our experiments did not include other stimuli during the test. Previous studies on the function of MPA neurons projecting to the vPAG have shown that these neurons respond to particular stimuli, such as CaMKIIα neurons responding to an object or prey, vglut2 neurons responding to stress, and galanin neurons responding to pups ( Wu et al, 2014 ; Kohl et al, 2018 ; Park et al, 2018 ; Zhang et al, 2021 ). Thus, it is plausible that there will be certain stimuli or conditions that could cause activation in the MPA vgat –vPAG circuit that in turn facilitate exploration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations